DEVELOPMENT OF PROTOTYPES OF THERAPEUTIC AND PROPHYLACTIC ANTIOXIDANT AGENTS BASED ON NATURAL BIOLOGICALLY ACTIVE COMPOUNDS OF TROPICOGENIC REPRESENTATIVES OF ORCHIDACEAE JUSS. - Ivannikov, R.; Laguta, I.; Stavinskaya, O.; Buyun, L. (Science and Innovation, 2021)
Introduction. Plant extracts and bioactive substances (BAS) of natural origin possess a high biological activity and a low toxicity, therefore they are widely used in cosmetic, pharmaceutical, and food industries. Problem Statement. Nowadays, about 50% of all medical drugs, dietary supplements, and herbal medicines is produced from natural sources, so the search for plants with a high content of BAS, the development of biotechnologies for BAS production, and the design of composites providing the most effective use of BAS are of great importance. Purpose. The purpose is to study tropical orchid collection for identification of plants with a high BAS content; to develop a procedure for growing promising species in vitro; to design drug prototypes on the basis of plants extracts, nanosized silica, and gelatin biopolymer. Materials and Methods. The extracts prepared from orchids leaves, silica, and gelatin have been used as auxiliary components for composites synthesis. Spectrophotometric, chromatographic, quantum-chemical, anatomo-morphological, physiological-biochemical, and biotechnological methods have been used in the research. Results. The species of orchids, which contain a significant amount of BAS with high antioxidant properties have been identified, the main components of orchids extracts have been distinguished. Sterile cultures of selected species have been obtained; protocols for their cultivation in vitro have been developed. Two types of bioactive composites have been prepared; the interaction of extracts components with silica surface and gelatin molecules has been studied. It has been shown that the materials composed of silica and orchid extracts possess a high storage stability and a prolonged desorption of several BAS, while the materials based on extracts, silica, and gelatin ensure gradual release of all the extracts components. Conclusions. The orchids are valuable sources of natural antioxidants. The designed composites are promising in terms of producing drug formulations for prolonged release of antioxidants.